Letra como Litoral de Água Viva: reflexões psicanalíticas sobre a escrita em Clarice Lispector e o gênero. - Silva, Eva Maria Lins (2020)
The present study had the purpose of researching for possible relations of concept of letter on the Lacanian theory with the literary work Água Viva and the gender debate. We propose to understand the letter in two fields, in the writing of the paper and in the writing of the body. Taking as a starting point the Lacanian concept of letter and perceiving the borders that the subject creates with his letter, either in literature or with the body. To achieve our goal, we conducted a bibliographic research, guided by the theoretical psychoanalytic field theory of Lacanian orientation. As well as we use other theoretical constructs belonging to other areas of knowledge such as literature and Gender Studies. We let ourselves be carried away by a floating listening that allowed us to work with the effects of the Claricean work, Água Viva. In writing the work, we gave ourselves over to creation, but we also had our theoretical contribution from Lacan and from gender studies. We identified that, through the use of the acoustic image of the signifiers, it was possible to think of creative solutions to problems that seemed unsolved, proposing, for example, a slide from the literary genre fiction to the fiction of the subject, inserted in the field of sexuality. Anchored in the relationship between psychoanalysis and literature, this methodological solution of the “significant slide” works as a bridge between subjects, initially disconnected. We believe that this work brings important contributions by providing the opening of new possibilities for dialogue between Psychoanalysis, literature and gender studies. It proposes to build a coastline between Lacan and Clarice Lispector, thereby opening up new possibilities for research. An unprecedented work is shown in the transposition between the literary genre and the sexuality genre. In addition, it was evident how the theoretical contributions of Lacanian oriented psychoanalysis, especially with the advances given by Lacan in his last teaching - with the notion of letter, formulas of sexuation, jouissance, not all phallic and feminine - can reaffirm how much psychoanalysis is up to the subjectivity of its time and how much it can establish a fruitful dialogue with other fields of knowledge.